HUMAN SECURITY AND LAND BORDERS CLOSURE: A HISTORICAL PERSPECTIVE - ISREAL SAMUEL; YAHAYA TOYIN LAWAL; GOD'SLOVE ZEBULON (International Studies Journal)
The paper examined how concerned of national interest and human security led to Nigeria land border closure in 2019.The paper employs the historical method to reviewed and analysed Data. The work adopted the liberal theoretical framework which justified trade liberalization and free movement of people and goods from one place to another as a gateway for modernization and economic development. The paper argued that, the best decision taken by Nigeria federal government was the closure of her land border which stimulate economic growth and enhanced human security. The major findings of the paper revealed that smuggling activities in Nigeria is due to porous nature of Nigeria land borders, consequently insecurity and inflation have been on the increase with serious security implications on the citizens wellbeing and security. The paper also revealed that what influenced government closure of the borders was due to proliferation of light and heavy weapons across the Nigeria borders hence the executive order for border closure in 2019.The paper concludes that despite federal government acclaimed success of border closure of the nation land borders the closure did not yield the desire results.